Prokaryotic community formation on polyethylene films incubated for six months in a tropical soil. (15th January 2021) - Zhelezova, A.D.; Zverev, A.O.; Zueva, A.I.; Leonov, V.D.; Rozanova, O.L.; Zuev, A.G.; Tiunov, A.V.
Abstract: Polyethylene film is one of the most common types of recalcitrant plastic waste materials. Information regarding the fate of plastic films in soil is scarce compared to the fate of plastic films in aquatic environments. The aim of this study was to evaluate the effects of soil fauna and of impregnation of polyethylene films with oil on the colonization of low-density polyethylene films by prokaryotic communities. The field experiment was performed in a monsoon tropical forest (Vietnam). Polyethylene films were incubated in thermally pre-defaunated soil isolated from the surrounding soil by a stainless steel mesh. Three mesh sizes were used, allowing access to different size groups of soil fauna. The diversity, taxonomic structure and co-occurrence patterns in prokaryotic communities were studied using high-throughput sequencing of 16S rRNA gene libraries. The prokaryotic communities that formed on polyethylene films were slightly different from those inhabiting the surrounding soil. Contrary to our expectations, no difference in the diversity of prokaryotes was observed between microcosms with different mesh sizes. Oil impregnation also had only a minor influence on the prokaryotic community structure. Polyethylene films incubated in microcosms with soil appeared to be colonized by various consortia of prokaryotes as a barren and inert surface. Graphical abstract: Image 1 Highlights: The effects of soil fauna and oil impregnation on the prokaryotic colonization of polyethylene films were studied. The field experiment was performed in a monsoon tropical forest (southern Vietnam). Soil fauna activity did not affect the structure or diversity of prokaryotic communities on polyethylene films. Polyethylene films appear to be colonized by various consortia of prokaryotes as a barren and inert surface.